Philippine statistical information sources and services 1970-1986 - Villalonga, Ma. Theresa T.; Buenviaje, Rufo Q.; Buenrostro, Juan Jr. C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1989)
The study attempts to bring in one compilation the Philippine statistical publications published from 1970 to 1986 by various government and private agencies. The bibliography is divided into two parts: Part one consists of the introduction and the historical developments of Philippine Statistical System; Part two consists of the bibliography proper. Title and subject indexes are provided.
Typescript.
Special Problem (Master of Library Science)
Keywords: Statistics -- Bibliography. -- Philippines